Formulation and Evaluation of Molexicam Orally Disintegrating Tablet (ODT) - Al Zomor, Abdulkarim K.; Al Nethary, Mohammed A. (Thamar University Journal of Natural & Applied Sciences, 2023)
The aim of the present study was to develop and evaluate an oral disintegrant tablet of meloxicam. Drug delivery systems became sophisticated and pharmaceutical scientists acquire a better understanding of the physicochemical and biochemical parameters pertinent to their performance. Over the past three decades, mouth dissolving or orally disintegrating tablets have gained considerable attention as a preferred alternative to conventional tablets due to better patient compliance. Orally is the most preferable route of drug administration which has some limited to drug candidate that show poor permeability across the gastric mucosa and those, which are sparingly soluble. A large majority of the new chemical entities and many new existing drug molecules are poorly soluble, thereby limiting their potential uses and increasing the difficulty of formulating bioavailable drug products, so lastly the purpose of this study was to grow mouth dissolve tablets of Meloxicam. Meloxicam is a non steroidal anti-inflammatory drug (NSAID) which a newer selective COX-1 inhibitor. Different five formulations were prepared in his study and evaluated. These tablets were prepared by direct compress procedure. Results: The results indicate that formulation number five is the best formula were friability is 0.65% < 1%, wetting time is 5.5 sec. and disintegration time is 18 sec.Dissolution test indicate that more than 75% of drug dissolve in the first 5min. and assay test is 99.1% which is within the pharmacopeia limit (90-110%). The systematic formulation approach helped in understanding the effect of formulation processing variables.